Designing A Web Based E-Rapor Information System Using SDLC Method - Wahyuni, Wahyuni; Rini, Faiza; Alfiriani, Adlia (Knowbase : International Journal of Knowledge in Database, 2023)
In the context of present educational challenges, the significance of computer technology is growing, aiming to improve administrative efficiency and communication among schools, teachers, and parents. Thus, it is essential to assess its influence on shaping a more contemporary and efficient education system, specifically in handling student grades through the adoption of web-based e-rapor systems. This research aims to simplify the teacher's task in administering student grades, reducing the time burden required in this process. The development method used is SDLC with a waterfall model. Data was obtained through field research, through observation and interviews. The research results show that this system is considered very good, with an average percentage of assessments by experts reaching 84.17%. Component assessment also shows good performance, such as functionality (87.5%), reliability (79.17%), usability (82.14%), efficiency (81.25%), maintainability (100%), and portability ( 75%). System users also gave very good ratings, with an average rating percentage reaching 86.36%. User component assessments include website appearance (85%), website menu (87.5%), website content (86%), user friendliness (83.33%), and usefulness (90%). The results of this research indicate that the web-based e-rapor information system is very suitable for use with excellent performance, responding to the demands of current educational needs.